Serine proteases activity is important for the interaction of nematophagous fungus Duddingtonia flagrans with infective larvae of trichostrongylides and free-living nematodes Panagrellus spp. Issue 8 (August 2015) - Cruz, Daniela G.; Costa, Luana M.; Rocha, Letícia O.; Retamal, Claudio A.; Vieira, Ricardo A.M.; Seabra, Sergio H.; Silva, Carlos P.; DaMatta, Renato A.; Santos, Clóvis P.
Abstract The nematode-trapping fungus Duddingtonia flagrans has been studied as a possible control method for gastrointestinal nematodes of livestock animals. These fungi capture and infect the nematode by cuticle penetration, immobilization, and digestion of the internal contents. It has been suggested that this sequence of events occurs by a combination of physical and enzymatical activities. The aim of this study was to investigate the participation of proteolytic enzymatic activity during the interaction of the nematophagous fungus D. flagrans with infective larvae of trichostrongylides and the free-living nematode Panagrellus spp. Protease inhibitors used interfered in the predatory activity of D. flagrans. However, only PMSF significantly reduced the mean number of Panagrellus spp. captured by D. flagrans in comparison with the control. The experiment with fluorogenic substrate showed that maximum urokinase activity during the interaction of the fungus with the infective larvae of trichostrongylides or Panagrellus spp. occurred within 7 or 1 h of incubation, respectively. The protease activity, especially of the serine class, may be important during the interaction between the fungus and nematodes.